Comparative analysis of macroeconomic performance and volatility before and after capital account liberalization: Cases of chile and Malaysia - Çiftçio?lu, Serhan; Colakoglu, Nuri (My University, 2012)
The main goal of the paper is to carry out a comparative analysis of experience of Chile and Malaysian economies (in terms of macroeconomic performance and volatility of selected indicators) before and after capital account liberalization. Our findings show that macroeconomic performance, particularly in terms of growth rate of GDP, inflation rate, investment and saving rates, respective ratios of export to import to GDP improved in both countries. While volatility experienced in the postliberalization period declined in case of Chile for all the parameters investigated, in case of Malaysia the results are mixed. One key finding is that in both countries, as theoretically expected, volatility of real private consumption fell sharply in the postliberalization period. © Serhan Ciftcioglu, Nuri Colakoglu, 2012.
Keywords: Chile; Liberalization; Macroeconomics; Malaysia; Volatility